Statistical Reliability Analysis for Assessing Bridge Structural Integrity: A Review Paper - Gustavo S. P. Primo; Ramon Silva; Francisco Evangelista; Marcos H. Oliveira (Infrastructures, 2025)
This article reviews methods for estimating the remaining service life of bridges, focusing on the statistical analysis of reliability indices, which aids in identifying risks and predicting structural failures. Among the methodologies examined, the First-Order Reliability Method (FORM) is highlighted for its effectiveness in calculating failure probabilities based on current deterioration and loading conditions. Sensitivity analysis is also discussed, as it pinpoints the variables that most significantly impact structural stability. Enhanced using the Finite Element Method (FEM), this method allows the simulation of structural behavior across different deterioration scenarios, improving the precision of failure predictions and optimizing maintenance planning. This review provides insight into how the integration of probabilistic methods and sensitivity analysis can enhance failure prediction and support more efficient maintenance planning for bridge structures.